PEMBELAJARAN IPS DENGAN MEDIA KOMIK STRIP DI KELAS 4 - Ayok Ariyanto dan Sigit Dwi Laksana (Universitas Muhammadiyah Ponorogo, 2017)
The use of comics as a learning media is very rare to find, the tendency of teachers lazy to use because it must first draw a strong reason teachers do not use this media. Comics as a learning medium is very powerful and can evoke students' understanding of the material because of the interesting storyline and the existence of images that are favored by children, researchers want to try to cultivate and introduce to the public and educators that the comic media can be an alternative learning meda, especially the comic strips which are the simplest and easiest types of comics. This introduction is done through an experimental study conducted in SDMT Ponorogo which incidentally as an elementary school favorite and excel in the field of academic and applied in class 4 with class considerations that have unique characteristics. It is expected that the results of this Research will be of great benefit to educators and learners in all classes in general.